Mejoramiento de la gestión de trámite documentario utilizando firma digital en el Proyecto Especial Alto Mayo - Moyobamba - Ibérico Suárez, Lee Ed (2013)
The Alto Mayo Special Project (PEAM) is a governmental institution belonged to the Regional Government of San Martin us a dependent execution unit, under this fact the PEAM has been implementing its actions with the combined use of Treasure resources, donations and External Credits. Therefore it has regulatory and administrative functions and also provides administrative procedure manuals (TUPA. Text of Administrative Procedures); these management tools are the source for the planning of management indicators on the process of documentary proceeding, which has a deficiency in growth file control of the organization and its dependencies. For the following research, the application of a documentary systematization process based on digital signature is proposed as a solution, in order to improve the process in self. This solution is designed as a measure system as focused as the analysis and design of organizational reality of PEAM. The methodologies and development solution tools software provide the easy form of registration and monitoring of documents, digital supporting files, process of control table to generate certification by digital signature of enabled users. The development of this document, guides the reader in gradual knowledge of the problem, the analysis and design of the alternative of solution. Legal considerations about technologies involving on digital signature and document scanning are evaluated.